FAILURE TO PAY TAX TAX MISDEMENOR OF TAX PAYER -PHYSICAL PERSON - Djokic, Minja S (NBP. Nauka, bezbednosti, policija, 2018)
Tax proceeding act prescribes numerous tax misdemeanors which are normatively divided into two categories. First category are general tax misdemeanors of legal persons and entrepreneurs, and the second are so called special tax misdemeanors. The subject of this paper is tax misdemeanor of tax payer who is a phisical person and who does not pay tax debt determined in his tax return or, respectively in decision of Tax administration. Our research is based primarily on legislation and available Serbian and international jurisprudence. We will point out that forementioned misdemeanor can be disputed based on the reach of its zone of incrimination. This paper will also show that it is possible to violate prohibition of double jeopardy principle at the expense of tax payers due to the systematic mismatch of tax law and tax administrative (process) law with provisions that prescribe tax misdemeanor. The final result of this paper and added value to Serbian tax law are our prepositions of legislation interventions de lege ferenda. We will suggest that tax misdemeanor from article 180, point 2 of Tax procedure and tax administration Law needs to be erased. We strongly argue that enforcement of tax collection needs to remain in tax enforcement procedure and that there is no legal justification to prosecute tax payers that are late on their tax payment. Tax administration has sufficient mechanisms to collect tax owed.